The Effect of Fixed Asset Intensity, Transfer Pricing, and Institutional Ownership on Tax Aggressiveness - Yuniati, Nining (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to inform the government, companies as taxpayers, and academics about the risks and factors that influence tax aggressiveness. This study is a descriptive quantitative study with secondary data from financial statements of basic materials sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. With the E-views 12 tool, panel data is estimated to obtain a Random Effect Model. Hypothesis testing indicates that fixed asset intensity has a significant and positive effect on tax aggressiveness. The transfer pricing and institutional ownership variables in this study do not affect tax aggressiveness.